Identifikasi Telur Cacing Ascaris Lumbricoides pada Lalapan Kubis di Warung Makan Pecel Lele Sepanjang Jalan Pasar Kemiri Kembangan Utara - Indrawan Indrawan (Jurnal Medical Laboratory, 2024)
Worm infections are still commonly found in Indonesia because of its location in the tropics. Worms are caused by various factors, one of which is consuming raw vegetables contaminated with intestinal parasites which are included in (Soil Transmitted Helmint), one of which is the egg of the worm Ascaris lumbricoides. Types of vegetables that allow transmission to occur are vegetables such as cabbage, because cabbage is often consumed raw or as fresh vegetables, for example, in the habit of Indonesians, fresh vegetables are part of the topping for pecel lele sellers, which still exist today. It is very likely that the cabbage vegetables sold from pecel catfish traders are contaminated because they are not clean when washing. The purpose of this study was to determine whether Ascaris lumbricoides worm eggs were present in fresh cabbage vegetables after being washed at pecel lele food stalls along Jalan Pasar Kemiri Kembangan Utara. This type of research is descriptive observational at the Kesosi STIK Laboratory, which describes the presence of Ascaris lumbricoides worm eggs in fresh vegetables of cabbage (Brassica oleracea). The sample was determined using a total sampling technique obtained from each Pecel Lele food stall along Jalan Pasar Kemiri Kembangan Utara, with a total sampling of 10 samples. This examination was carried out using the sedimentation method. The results showed that 9 samples or 90% did not find Ascaris lumbricoides worm eggs and 1 sample or 10% found contamination of Ascaris lumbricoides worm eggs. The conclusion is that cabbage or cabbage (Brassica oleracea) at Pecel Lele food stalls along Jalan Pasar Kemiri Kembangan Utara still found Ascaris lumbricoides worm eggs.